The Effects of Chronic Administration of Hydrogen Sulfide on Anxiety and Depression-like Behaviors in Streptozotocin Rat Model of Alzheimer’s Disease - Haghdopst, Hashem; Esmaeili, Mohammad Hossein; Sofiabadi, Mohammad; Solimany, Pouria; Esmaeili, Samira (Majallah-i dānishgāh-i ʻulūm-i pizishkī-i Ardabīl, 2021)
Background & objectives: Alzheimer’s disease (AD) patients suffer from anxiety and depression. Sodium hydrosulfide (NaHS) can remit the depressive-like and anxiety-like behaviors induced by diabetes mellitus. We aimed to investigate the effects of chronic administration of hydrogen sulfide on depressive and anxiety-like behaviors in the Streptozotocin (STZ) rat model of AD. Methods: Animals were divided into: Control, NaHS, and Alzheimer’s rats group include (STZ, STZ + Saline and STZ + NaHS groups) which were the Alzheimer’s rats and received Saline and NaHS (5.6 mg/kg per d) for 21 days. For induction of AD, STZ (3 mg/kg, 10 μl/injection site) was administered into the lateral ventricles. The behavioral consequences were assessed using plus maze, forced swim and sucrose preference tests. Results: Our results showed that intracerebroventricular (i.c.v.) injection of STZ decreased the percentage of open arm time and entries, indicating anxiety-like effects. It also increased the duration of immobility time and decreased the percentage of sucrose preference indicating depression-like effects. Sodium hydrosulfide administration in STZ-treated rats increased the percentage of open arm time and entries, indicating anxiolytic-like effects. It also decreased the duration of immobility time and increased the percentage of sucrose preference, indicating antidepressant-like effects. Conclusion: STZ administration can induce depression- and anxiety-like symptoms in rats, and Sodium hydrosulfide treatment, decreased the depression- and anxiety-like symptoms in STZ rat Model of AD, suggests that Sodium hydrosulfide can be useful in the treatment of affective disorders in AD patients.